Analysis of Delays in Development Projects View Unit Villa Marina Opus Bay - Irlas Helen Pakpahan; Mulia Pamadi (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2022)
Practical work is a mandatory course carried out by final year students before the thesis is completed, with the aim of gaining practical experience which is carried out for approximately 3 months in the field. Where practical work is carried out from October 25, 2021 to January 25, 2022. In carrying out practical work activities the author serves as a field supervisor and finds obstacles in a project for the construction of the Show Unit Villa Marina Opus Bay, there are several constraining factors during the project work process. This affects the implementation time which results in not being completed on time. The obstacles include material delays and lack of manpower. In carrying out these activities, data collection was carried out using field observations and field documentation.